Bulk titanium nitride ceramics – Significant enhancement of hardness by silicon nitride addition, nanostructuring and high pressure sintering. Issue 10 (September 2015) - Bläß, U.W.; Barsukova, T.; Schwarz, M.R.; Köhler, A.; Schimpf, C.; Petrusha, I.A.; Mühle, U.; Rafaja, D.; Kroke, E.
Abstract Dense nanocomposites consisting of titanium nitride (TiN) and 1.7–8.1 mol% silicon nitride (a-Si3N4) have been prepared by high-pressure sintering at 6.5 GPa and at temperatures up to 1300 °C. Microstructure, hardness, indentation fracture toughness, elastic modulus and the correlation of these parameters to the silicon nitride content of the obtained TiN–Si3N4 ceramics have been determined. The results demonstrate that even the addition of small amounts of Si3N4 leads to a considerable increase in Vickers hardness to HV500 g ∼ 25 GPa and indentation fracture toughness up to 6 MPa m½. This significant enhancement of mechanical properties can be related to interfacial bonds between titanium nitride crystals strengthened by nano-size effects and amorphous silicon nitride forming an intergranular matrix. Realignment and rotation of such interlocked titanium nitride crystallites under deformational stress is suppressed and crack propagation reduced by a crack deflection mechanism.